Forces and Trauma Associated with Minimally Invasive Image-Guided Cochlear Implantation. (April 2014) - Rohani, Pooyan; Pile, Jason; Kahrs, Lueder A.; Balachandran, Ramya; Blachon, Grégoire S.; Simaan, Nabil; Labadie, Robert F.
Objective: Minimally invasive image-guided cochlear implantation (CI) utilizes a patient-customized microstereotactic frame to access the cochlea via a single drill-pass. We investigate the average force and trauma associated with the insertion of lateral wall CI electrodes using this technique. Study Design: Assessment using cadaveric temporal bones. Setting: Laboratory setup. Subjects and Methods: Microstereotactic frames for 6 fresh cadaveric temporal bones were built using CT scans to determine an optimal drill path following which drilling was performed. CI electrodes were inserted using surgical forceps to manually advance the CI electrode array, via the drilled tunnel, into the cochlea. Forces were recorded using a 6-axis load sensor placed under the temporal bone during the insertion of lateral wall electrode arrays (2 each of Nucleus CI422, MED-EL standard, and modified MED-EL electrodes with stiffeners). Tissue histology was performed by microdissection of the otic capsule and apical photo documentation of electrode position and intracochlear tissue. Results: After drilling, CT scanning demonstrated successful access to cochlea in all 6 bones. Average insertion forces ranged from 0.009 to 0.078 N. Peak forces were in the range of 0.056 to 0.469 N. Tissue histology showed complete scala tympani insertion in 5 specimens and scala vestibuli insertion in the remaining specimen with depth of insertion ranging from 360° to 600°. No intracochlear trauma was identified. Conclusion: The use of lateral wall electrodes with the minimally invasive image-guided CI approach was associated with insertion forces comparable to traditional CI surgery. Deep insertions were obtained without identifiable trauma.